Global Value Chains in economic development - Hansjörg Herr; Petra Dünhaupt (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2019)
Global Value Chains (GVCs) started to play an increasing and key role in the global economy from the 1990s on. The market mechanism in GVCs supports industrialisation in the Global South and under certain conditions product and process upgrading. But GVCs do not lead to the catching-up of countries in the sense of them approaching real GDP per capita levels comparable with developed countries. These arguments are supported by a critical interpretation of the traditional trade theory, the New Trade Theory and specific approaches to explain GVCs, especially different governance structures and power relationships. Several case studies support these arguments. For catching-up, countries need comprehensive horizontal and vertical industrial policy and policies for social coherence. The small number of countries which managed to catch up did this in different variations.
Keywords: F16; F23; O19; O25; 330; Global Value Chains; Under-development; Rent-seeking; Industrial Policy